Fine mapping of the MHC region identifies major independent variants associated with Han Chinese primary biliary cholangitis. Issue 107 (February 2020) - Wang, Chan; Zheng, Xiaodong; Tang, Ruqi; Han, Chongxu; Jiang, Yuzhang; Wu, Jian; Shao, Youlin; Gao, Yueqiu; Yu, Jianjiang; Hu, Zhigang; Zang, Zhidong; Zhao, Yi; et al.
Abstract: The genetic association of primary biliary cholangitis with major histocompatibility complex (MHC) has been widely confirmed among different ethnicities. To map specific MHC region variants associated with PBC in a Han Chinese cohort, we imputed HLA antigens and amino acids (AA) in 1126 PBC cases and 1770 healthy control subjects using a Han-MHC reference database. We demonstrate that HLA-DRB1 and/or HLA-DQB1 contributed the strongest signals, and that HLA-DPB1 was a separate independent locus. Regression analyses with classical HLA alleles indicate that HLA-DQB1*03:01 or HLA-DQβ1-Pro55, HLA-DPB1*17:01 or HLA-DPβ1-Asp84 and HLA-DRB1*08:03 could largely explain MHC association with PBC. Forward stepwise regression analyses with HLA amino acid variants localize the major signals to HLA-DRβ1-Ala74, HLA-DQβ1-Pro55 and HLA-DPβ1-Asp84. Electrostatic potential calculations implicated AA variations at HLA-DQβ1 position 55 and HLA-DPβ1 position 84 as critical to peptide binding properties. Furthermore, although several critical Han Chinese AA variants differed from those shown in European populations, the predicted effects on antigen binding are likely to be very similar or identical and underlie the major component of MHC association with PBC. Highlights: HLA-DRB1 and/or HLA-DQB1 contributed the most signals, and HLA-DPB1 was a separately independent locus. HLA-DQB1*03:01, HLA-DPB1*17:01 and HLA-DRB1*08:03 could largely explain MHC association with PBC. HLA-DRβ1-Ala74, HLA-DQβ1-Pro55 and HLA-DPβ1-Asp84 were major MHC residues independently associate with PBC. Critical Han Chinese AA variants on antigen binding groove underlay the major component of MHC association with PBC.